2019
DOI: 10.1039/c9cp01121h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and localized states in amorphous Si and hydrogenated amorphous Si

Abstract: Calculated DOS of a-Si:H close to the band gap for different H concentrations in the case of (a) thermodynamic and (b) kinetic H addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 77 publications
2
21
0
Order By: Relevance
“…Therefore PCM measurements revealed that the origin of defect states might be a result of different type of general structural disorders beyond DBs. [15,16] In addition to experimental work, several recent theoretical and computational work have shown highly strained bonds significantly contributing to midgap states and DBs [17,18].…”
Section: B Defects In Amorphous Simentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore PCM measurements revealed that the origin of defect states might be a result of different type of general structural disorders beyond DBs. [15,16] In addition to experimental work, several recent theoretical and computational work have shown highly strained bonds significantly contributing to midgap states and DBs [17,18].…”
Section: B Defects In Amorphous Simentioning
confidence: 98%
“…Thus, the creation of accurate melt-quench a-Si requires significant DFT input. Even then, reaching experimental-level accuracy is still difficult, and this process can only yield structures on the edge of acceptability [18].…”
Section: A Creating the Amorphous/crystalline Stacks: Machine-learnin...mentioning
confidence: 99%
“…It is reported that in the strained Si network, the overal stain energy can be reduced by hydrogenation with commensurate reduction of mid-gap states and orbital localization. [17] H atom to a strained bond is associated with a change in the long range order, subsequently resulting in strain reduction and more stabilization. Increasing the structural order leads to strain release from the whole strained-Si structure with the replacement of weak strained Si-Si bonds by strong Si-Si bonds.…”
Section: -1 IV Characteristics Under the Mechanical Bending Stressmentioning
confidence: 99%
“…Also, the midgap state reduction can be from the replacement of relatively weak Si-Si bonds by strong Si-H bonds. [17] In strained poly-Si, the more strained bonds exist, the more bonds are going to be hydrogenated, where H is supplied from the PI substrate. And this comes to the reduction of midgap states and also the extracted Ntrap.…”
Section: -1 IV Characteristics Under the Mechanical Bending Stressmentioning
confidence: 99%
“…Among various key factors to improve the performance, hydrogen concentration is one of the most relevant ones [8]. It has been shown that the hydrogenation of a-Si has a beneficial effect in reducing the overall strain energy of the a-Si network [9]. Legesse et al investigated the optical gap and the electron mobility with VASP [10] and proposed three regimes of the hydrogen concentration; in the unsaturated regime, both the optical gap and the mobility increase with the increase of hydrogen concentration until they converge to some constant values in the saturated regime.…”
Section: Introductionmentioning
confidence: 99%